PENERAPAN METODE SCAFFOLDING DALAM MENINGKATKAN KEMAMPUAN MENULIS KARYA TULIS ILMIAH PADA SISWA - Afifah Shinta Nur Aida; Afenia Wulan Cahya; Amanu; Indayani; Setiyana Indradini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research (CAR) was conducted to improve the scientific writing skills of eleventh-grade students (Class XI M2) at SMA Intensif Taruna Pembangunan Surabaya through the application of the scaffolding method. The low ability of students to compose scientific papers systematically, particularly in structuring the background, formulating problems, and using proper academic language, motivated this study. The research followed the Kemmis and Mc. Taggart spiral model, implemented in two cycles consisting of planning, action, observation, and reflection. Data were collected through tests, observation, and documentation, then analyzed descriptively using means, completeness percentages, and the Normalized Gain (N-Gain). The results showed a consistent improvement in students' scientific writing ability across the two cycles: the mean pretest, posttest, and N-Gain scores in Cycle I were lower than those obtained in Cycle II, indicating that the gradual scaffolding provided by the teacher increasingly supported students' independence in composing scientific texts. These findings confirm that a structured, gradually reduced scaffolding approach is effective in enhancing students' scientific writing competence and can be considered an alternative instructional strategy for Indonesian language teachers in senior high schools.